The patellar compression angle: a new, accurate diagnostic angle for lateral patellar compression syndrome - Xiaokang Gao; Jinwei Liu; Jingyu Zhang; Zhitao Xie; Chengyue Yu; Yufei Yuan; Leming Mou; Weiguo Xu (Journal of Orthopaedic Surgery and Research)
Abstract Background Lateral patellar compression syndrome (LPCS) is a common cause of anterior knee pain. Early diagnosis of LPCS using an accurate radiological examination is, therefore, important. However, the currently used radiological examinations for detecting LPCS are poor diagnostic indicators. Therefore, the aim of this study was to establish a new diagnostic imaging examination for LPCS and evaluate its accuracy in comparison with conventional examinations. Methods From June 2020 to May 2023, a retrospective analysis was conducted on 72 patients in the LPCS group and 140 patients in the Control group, all of whom underwent axial radiographs of the patella and knee MRI. The patellar compression angle (PCA), Tilting angle (TA), Congruence angle (CA), Grelsamer angle (AG), and Lateral patellofemoral angle (LPA) were used and compared statistically for their accuracy in terms of diagnosing LPCS. Results The area under the receiver operating characteristic curve (ROC) for the PCA was 0.87, which was the highest among the five examinations. ROC analysis revealed that a smaller PCA, less than 14.7°, was associated with LPCS, with the highest sensitivity (80.6%), specificity (82.9%), accuracy (82.1%), positive predictive value (PPV, 70.7%), negative predictive value (NPV, 89.2%), positive likelihood ratio (PLR, 4.71), and lowest negative likelihood ratio (NLR, 0.23) compared with the other four examinations. The interobserver reproducibility of the PCA was good, with an intraclass correlation coefficients (ICCs) of 0.85. Conclusions The PCA can detect LPCS with a moderate diagnostic performance and could, therefore, might be a new angle for the diagnosis of LPCS in clinical settings.